The Effect of Dragon Fruit Skin Powder Fermented in The Rations Toward on Organes In Sheet Chicken (Lohmann Brown) Age 21 Weeks - Diana, I P. R. S.; Wirapartha, M.; Dewi, G. A. M. K. (Jurnal Peternakan Tropika; Vol 7 No 2 (2019), 2019)
This study aims to determine the effect of fermented dragon fruit skin flour on rations on organs in laying hens ( Lohmann Brown ) aged 21 weeks. This research has been carried out at the Field Laboratory (Teaching Farm) of the Faculty of Animal Husbandry Campus, Jimbaran, Badung, Bali for 15 months. The design used was Completely Randomized Design (CRD) with 3 treatments and 5 replications, each replication consisted of 3 chickens, total of 45 chickens were used. The treatments given are fermented dragon fruit skin ration, 5% fermented dragon fruit skin ration and commercial R2 ansum. The variables observed were cut weight, heart weight, liver percentage, heart weight, heart percentage, bile weight, percentage of bile, spleen weight, and percentage of spleen. The results showed variable weight, weight, spleen weight, percentage of bile and spleen were not significantly different between treatments R0, R1, and R2 (P>0.05). Heart weight, bile weight, liver percentage and heart percentage treatment R1 and R2 were significantly different (P<0.05) compared to R0. From the results of the study it can be concluded that giving rations with 5% fermented dragon fruit skin and commercial rations affect heart weight, bile weight, liver percentage, heart percentage (P>0.05) and does not affect cut weight, liver weight, spleen weight, percentage of bile and percentage of spleen (P<0.05) in Lohmann Brown chicken age of 21 weeks. Keywords : c hicken , lohmann brown, internal organ, dragon fruit skin, saccharomyces cerevisiae .